Exploring Anti-Bullying Strategies in Islamic Boarding Schools: A Comparative Study of Indonesia and Malaysia - Abdurrohim, Abdurrohim; Fitriani, Ely; Akbari, M Yudo Agresi; Bachtiyar, Machfud; Fuad, Ah Zakki; Syaifudin, Mokhamad (STAI Hubbulwathan Duri, 2024)
The phenomenon of bullying is a serious and concerning problem, especially in educational environments such as schools and Islamic boarding schools. This research aims to explore educational models and approaches used in preventing and dealing with bullying in Islamic boarding schools in Indonesia and Malaysia, using a Systematic Literature Review (SLR) approach which involves systematic identification, evaluation, and synthesis of relevant research. Google Scholar and ERIC were chosen because of their broad academic coverage and access to educational and psychological journals. Of the initial 290 articles, 40 articles were excluded due to duplication, irrelevance, or not meeting established inclusion criteria. The research results show that there is a trend in anti-bullying education models in Islamic boarding schools varying from prevention to intervention. Overall, the approach used to prevent and handle bullying in Islamic boarding schools in Indonesia and Malaysia shows a commitment to creating a safe and conducive educational environment. Thus, the results of this research will be a contribution to policy makers and Islamic boarding schools in preparing anti-bullying programs in the Islamic education environment.